Effectiveness of a Superset-Based Physical Fitness Learning Program in Improving Muscular Strength among Male Adolescents in a Nonformal Learning Environment - Adiakhmad, Teja Timur; Putro, Waskito Aji Suryo; Mulloh, Farcham (Program Magister Teknologi Pendidikan Universitas Jambi, 2026)
Physical fitness learning plays an important role in supporting adolescents’ physical development and promoting healthy lifestyles through meaningful learning experiences. However, the effectiveness of physical fitness programs is often influenced by the learning strategies used to engage participants and optimize learning outcomes. One strategy that can be implemented in nonformal learning environments is the superset method, which combines two consecutive physical activities with minimal rest intervals. This study aimed to examine the effectiveness of a superset-based physical fitness learning program in improving the physical fitness learning outcomes of male adolescents, as indicated by muscle strength development. This study employed a quantitative approach using a quasi-experimental design with a pretest-posttest control group design. The participants were 30 male adolescents aged 13–17 years who were divided into an experimental group (n = 15) and a control group (n = 15). The experimental group participated in a superset-based physical fitness learning program for eight weeks, while the control group followed a conventional fitness learning program. Data were collected using the One Repetition Maximum (1-RM) test on bench press and squat exercises and analyzed using t-tests. The results showed that the experimental group achieved greater improvements in muscle strength than the control group. Bench press performance increased by 18.5%, while squat performance increased by 22.4%, with significant differences between groups (p < 0.01). These findings indicate that the superset method can serve as an effective learning strategy for enhancing physical fitness learning outcomes in nonformal education settings.